Forecasting The Development of IKN (New National Capital) in Sustainable Development, Indonesia - Rita Kalalinggi; Muhammad Hisdar; Mia Sarmiasih; Angga Kusuma Wijaya (Journal of Governance and Public Policy, 2023)
This study aims to describe related forecasting of New National Capital (IKN) development in sustainable development. This research uses a literature study that focuses on media and reports. The following are CNN Indonesia, Tempo, Jawapos, and reports from Bappenas, State Secretariat, and DPR. Go.id. The results of this study indicate that the IKN development forecast is formulated for smart transportation, smart grid, and green building and the development process must meet the principles of justice, participation, and gender equality (especially for women) which are important foundations in sustainable development. In addition, there are several challenges faced by IKN in the future based on the findings in the mass media. First, integration is needed based on basic conditions where all design and construction must be based on current topographic and geological conditions. Second, land grading and all infrastructure plans must refer to drainage plans to prevent flood disasters. Third, coordination of underground infrastructure is required. According to Takehiro, one thing to pay attention to is securing the right of way (ROW) area, especially for manholes and larger structures such as sewer lift pumps. Fourth, it is necessary to prepare space to ensure the accessibility of future expansion. IKN development must also pay attention to economic, social, and ecological impacts. This is because development tends to only think about infrastructure and large-scale land clearing with economic interests, which fail.